Development of Wind Turbine Generator and Solar Hybrid Power System Model for Rural Electrification - Ola Austin Oshin (Newinera Publisher, 2022)
The countries that are most energy-consuming, where there are industrial developments, where the energy demand is highest are the advanced and developing countries in the world (Mustafa, 2018). For instance, the average power per capital (watts per person) in the United States is 1,377 Watts. In Canada, it is as high as 1,704 Watts per person and in South Africa; it is 445 Watts per person. The average power per capital in Australia is 1,112 Watts and in New Zealand it is 1,020 W per person. Whereas, the average power per capital (watts per person) in Nigeria is 14 W per person. (Austin, O. O et.al, 2020). Also, power supply in many parts of Africa is erratic and characterized with a lot of faults and outages. In Nigeria, it is estimated that only 40 % of Nigerians are connected to the national grid and the connected population are exposed to frequent power outages (Abubakar et al, 2015, Austin O.A, 2020). Unfortunately, the effects of incessant power supply have destroyed many industrial activities, reduced employment and has increased crime activities in many parts of the continent (Africa). Therefore, in order to provide urgent solution to these problems and satisfy the high energy demand in African residential and industrial environments, electrical energy should be reliable, aﬀordable, effective, and sustainable. This calls for an urgent establishment of alternative Renewable Hybrid Power Supply System which will provide continuous, reliable and effective power supply to the consumers.